Analisis Pelaksanaan Supervisi Akademik Kepala Sekolah di Sekolah Dasar - Sherly Dwi Amelia; Imam Ahyar; Wilda Ummairah; Hanif Anwar; Lukman (Mataram University, 2026)
This study aims to analyze the implementation of academic supervision by elementary school principals in improving the quality of learning. The study employed a qualitative descriptive approach and was conducted at SD 2 Rumak, West Lombok Regency, during the second semester of the 2025/2026 academic year. The research subjects consisted of the principal, classroom teachers, and subject teachers selected through purposive sampling based on their involvement in academic supervision activities. Data collection techniques included participant observation, structured interviews, and documentation, with data analysis using the Miles and Huberman model, which encompasses data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of academic supervision has proceeded systematically through the stages of planning, implementation, feedback, and follow-up. Planning is carried out in a participatory manner involving teachers, while supervision is conducted through direct classroom observation using clear assessment tools. Feedback is provided constructively and followed up with guidance and follow-up supervision. Academic supervision has a positive impact on improving the quality of learning, such as the use of more varied methods, more effective classroom management, and increased teacher-student interaction. The findings reveal that academic supervision contributes to improving teachers' instructional practices, particularly in the use of varied teaching methods, classroom management, and teacher–student interaction. Constructive feedback and systematic follow-up were also found to play an important role in improving learning quality. However, the implementation of supervision still faces challenges, such as time constraints, scheduling conflicts, and differences in teacher readiness. Therefore, strengthening the management of supervision is necessary to ensure it is more optimal and sustainable.